Mechanical Properties of Lightweight Foamed Concrete With Ceramic Tile Wastes as Partial Cement Replacement Material - Lim, Siong Kang; Lee, Yee Ling; Yew, Ming Kun; Ng, Wen Wei; Lee, Foo Wei; Kwong, Kok Zee; Lim, Jee Hock (Frontiers in Built Environment, 2022)
The production of concrete emits greenhouse gases which aggravate global warming. In the meanwhile, ceramic tile wastes generated from manufacturing factories, construction sites and building demolition projects disposed of by landfills create land and water pollution. Therefore, in this study, the suitability of ceramic tile wastes (CTW) in powder form to partially replace cement in lightweight foamed concrete was investigated with the aim to discover a greener construction material. Once the research outputs show that the ceramic tile dust is appropriate to act as a replacer, environmental impact on air, land and water pollution can all be reduced. Three types of lightweight foamed concrete with 0 %, 25 % and 50 % ceramic tile wastes as partial cement replacement material were prepared with a target density of 1200 kg/m³, namely LFC-CTW0, LFC-CTW25 and LFC-CTW50 respectively. The effects of ceramic tile wastes on the engineering properties of lightweight foamed concrete were investigated. Concrete specimens were water cured and tested for various mechanical properties at the concrete ages of 7, 28 and 56 days. Results from the lab experiments showed that the incorporation of 25 % ceramic tile wastes into lightweight foamed concrete was comparably feasible than that of 50 %. LFC-CTW25 performed better than LFC-CTW0 for the splitting tensile strength test at Day-56. The results for the compressive strength test, modulus of elasticity and compressive toughness test showed a minor reduction after the incorporation of ceramic tile wastes. Based on the results, it can be concluded that it is feasible to use ceramic tile wastes up to 25% as partial cement replacement material to produce foamed concrete.